Pendekatan Politik Kriminal Secara Integral Dan Kausatif Dalam Penanggulangan Kebakaran Hutan Dan Lahan - ALFARISI, FADLI (The Prosecutor Law Review, 2024)
Forest and land fires (Karhutla) in Indonesia have caused massive damage to forest areas. Even the haze that passes through neighboring countries has an impact on Indonesia's relations in ASEAN. The state is obliged to manage and protect the environment through integral law enforcement between criminal and social policies that combine proportional repressive and preventive efforts as well as a causative approach to tackle crime. The prosecutor's office as law enforcer must understand the direction and policy of national development in dealing with forest and land fires. The research method used is normative research to find out how positive law is applied in a particular problem. Based on the research results, it is necessary to develop a comprehensive environmental management legal system to ensure legal certainty for the management of natural resources. One of them is through the multidoor system method, which is a case resolution mechanism using various interrelated statutory instruments. Conclusion to realize an integral and causative criminal political approach in dealing with forest and land fires through penal and non-penal means.